Nutrigardens for increased farmer income and food security in Kiphire, Nagaland - Bordoloi, L. J.; Kumar, Sunil; Karibasappa, C. S. (Indian Farming, 2025)
In Kiphire district, a remarkable transformation has taken place through the adoption of nutrigarden practices, a chemical-free approach to farming. Over 500 farmers have established nutrigardens, covering 200 ha, and noticed a 30% increase in crop yields and 25% rise in income. This initiative has not only improved soil health and biodiversity but also empowered farmers, especially women,with knowledge and skills to manage their own food systems. The success of Nutrigarden in Kiphire serves as a model for sustainable agriculture, demonstrating its potential to transform lives, environments, and communities. This initiative has also led to the formation of farmers' groups, facilitating knowledge sharing, resource exchange, and collective marketing efforts. As a result, Kiphire has become a beacon of sustainable agriculture, showcasing the power of community empowerment and dedicated support in transforming farming practices and improving livelihoods.